Review Peluang dan Tantangan Sukuk di Masa Pandemi Covid-19 sebagai Instrumen Keuangan Syariah Indonesia - Ma’ruf, Faried (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2021)
The Islamic finance industry has felt the economic driving force and the benefits of Sukuk as a sharia financial instrument for development funding although the impact is still insignificant. The main problem of not achieving the acceleration of Sukuk in Indonesia has become a statement by many people, so it is necessary to carry out continuous studies regarding its development. This study aims to identify opportunities and challenges as well as inhibiting factors for their development using the Pareto principle analysis. The identification results reveal that the understanding of issuers and investors and the public about Sukuk is still lacking, incentives for Sukuk are also low, the problem of Sukuk liquidity is lower than conventional bond instruments. Complementing the results of this study on Sukuk suggests that the main solution to the low development of Sukuk instruments is the need for incentive policies, regulations, which can encourage corporations to choose Sukuk as a means of investment.